Penggunaan Beberapa Konsentrasi Ekstrak Umbi Gadung (Dioscorea hispida Dennst.) dalam Mengendalikan Hama Walang Sangit (Leptocorisa acuta T.) pada Tanaman padi Gogo (Oryza sativa L.) di Lapangan. - Agusman Harefa; Hafis Fauzana; Desita Salbiah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
Upland rice prouction (Oryza sativa L.) in Riau Province was lower than the   previous year. One of the main constraints of upland rice is one of which is rice bug pest attack (Leptocorisa acuta T.). Eco-friendly pest  controls are offered using pestiside vegetables of gadung tuber extract (Dioscorea hispida Dennst). The aim of  the study was to obtain the concentration of  gadung tuber extract which was effective in controlling the stink bug pest on upland rice plants in the field. The research has been implemented in the experimental garden (green house), Faculty of Agriculture, University of Riau which from January to April 2018. The research is prepared using a completely randomized design (CRD) with 5 treatments and 4 replictions, ie the concentration of  gadung tuber extract 80,85,90,95, and 100 grams/liter water. The observed Parameters are, morphology changes and behavior, the start time of the death (hours), lethal time 50 (hours),  daily mortality (%), total mortality (%), temperature and humidity.  The results showed that the concentration of 90 grams/liter of water was an effective concentration for controlling rice bug pest control with an initial death time of 3.50 hours, lethal time 50 15.25 hours after application and a total mortality of 85%. Keywords: Upland rice plants (Oryza sativa L.), Rice bug (Leptocorisa acuta T.), Vegetable pesticides, Gadung tuber extract (Dioscorea hispida Dennst),